2021
DOI: 10.1155/2021/8813498
|View full text |Cite
|
Sign up to set email alerts
|

No Early Effect of Intrathecal Rituximab in Progressive Multiple Sclerosis (EFFRITE Clinical Trial)

Abstract: Background. The progressive phase of multiple sclerosis (MS) is characterized by an intrathecal (IT) compartmentalization of inflammation, involving B-cells within meningeal follicles, and resisting all the available immunosuppressive treatments. A new therapeutic paradigm may be to target this inflammation by injecting immunosuppressive drugs inside the central nervous system compartment. Methods. We designed a single-center, open-label, randomized, controlled, phase II study designed to evaluate the safety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…There is no compelling biological explanation presented in the literature providing a rationale as to why rituximab may be able to cross the BBB whereas other monoclonal antibodies are seemingly restricted to the periphery, and it may be that detection of low levels of rituximab in the CNS is confounded by the methods used in the studies reported to date (Petereit and Rubbert-Roth, 2009;Hagens et al, 2018). Moreover, recent clinical studies of intrathecally administered rituximab in patients with progressive MS have reported that treatment does not halt disease progression (Bergman et al, 2021(Bergman et al, , 2018Bonnan et al, 2021).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…There is no compelling biological explanation presented in the literature providing a rationale as to why rituximab may be able to cross the BBB whereas other monoclonal antibodies are seemingly restricted to the periphery, and it may be that detection of low levels of rituximab in the CNS is confounded by the methods used in the studies reported to date (Petereit and Rubbert-Roth, 2009;Hagens et al, 2018). Moreover, recent clinical studies of intrathecally administered rituximab in patients with progressive MS have reported that treatment does not halt disease progression (Bergman et al, 2021(Bergman et al, , 2018Bonnan et al, 2021).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Intrathecal rituximab resulted in a significant and sustained reduction in circulating B cells, but only a transient drop in CSF B cells and unchanged brain imaging outcomes during the 24-week follow-up period [ 181 ]. In the open-label phase II trial EFFRITE (NCT02545959), 10 patients were randomized into control group ( n = 2), intrathecal rituximab group (20 mg) ( n = 4), or intravenous (375 mg/m 2 ) plus intrathecal (20 mg) rituximab group ( n = 4) [ 182 ]. Patients received the therapy once and clinical, blood, MRI, and CSF assessments at several points in time during the one-year follow-up.…”
Section: Failed Mabs In Progressive Multiple Sclerosis With Otherwise...mentioning
confidence: 99%
“…Clinical parameters remained stable and leptomeningeal enhancements remained unchanged. Soluble CD21 (sCD21), which is a marker of B-cell pool, was decreased in serum but not in CSF after rituximab [ 182 ].…”
Section: Failed Mabs In Progressive Multiple Sclerosis With Otherwise...mentioning
confidence: 99%
See 2 more Smart Citations